In-Vivo Anti-Malarial Activity of 80% Methanol Leaf Extract of Croton Dichogamus Pax and Ehretia Cymosa Thonn in Plasmodium Berghei Infected Mice - Hashim D; Umer S; Hymete A; Mekonnen Y (Journal of Experimental Pharmacology, 2024)
Desta Hashim,1,2 Shemsu Umer,2 Ariaya Hymete,3 Yalemtsehay Mekonnen4 1Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Pharmaceutical Chemistry and Pharmacognosy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 4Department of Zoological Sciences, College of Natural and Computational Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Shemsu Umer, Email shemsu.umer@aau.edu.etBackground: Malaria is causing high mortality and morbidity due to Plasmodium’s resistance to currently available anti-malarial drugs and mosquito’s resistance to insecticides. Thus, there is a critical need to search for novel anti-malarial drugs from natural sources. Therefore, this study investigated in vivo antimalarial activities of two Ethiopian medicinal plants, Croton dichogamus Pax and Ehretia cymosa Thonn, in Plasmodium berghei infected Swiss albino mice.Methods: Soxhlet extraction method using 80% methanol as a solvent was used to prepare crude extracts of the two plants. Acute oral toxicity and 4-day suppressive in vivo antimalarial activity tests were performed on healthy female mice and P. berghei infected male mice, respectively. Antimalarial activity of the crude extracts at doses of 100, 200, and 400 mg/kg and the standard drug, chloroquine were used to assesse in Plasmodium berghei infected Swiss albino mice. Parasitemia level, packed cell volume, body weight, and rectal temperature of the mice were determined before infection (day 0) and after treatment (day 4). Survival time was determined by recording the date on which the mice died, considering the date of infection as day 0. The recorded data were analyzed using ANOVA and SPSS version 24.Results: The result of the acute toxicity study revealed that the crude extracts were non-toxic at doses up to 2 g/kg. The extract of E. cymosa suppressed parasitemia level by 66.28, 63.44 and 63.14% at 400, 200, and 100mg/kg, levels while C. dichogamus extract suppressed parasitemia level by 45.29% at a dose of 400mg/kg. The remaining two dose levels of C.dichogamus extract suppressed parasitemia level by < 30%.Conclusion: C. dichogamus and E. cymosa showed anti-plasmodial activities. E. cymosa exhibited a more pronounced anti-plasmodial effect than C. dichogamus. The activities of both plants observed in this study support their traditional use as antimalarial drugs. Further studies on these plants using solvent fractions are required to identify their active ingredients.Keywords: malaria, antiplasmodium, croton dichogamus, ehretia cymosa, P.berghei